Collective dynamics of domain structures in liquid crystalline lipid bilayers - V. N. Kadantsev; A. N. Goltsov (Российский технологический журнал)
Objectives. Numerous studies of biosystems indicate the distinct role of quasi-one-dimensional molecular structures in the transport of energy, charges, and information. Of particular interest are the studies on the collective dynamics of quasi-one-dimensional lateral structures in liquid crystalline membranes and the possibility of local excitation transfer through such structures. In this paper, we developed a model for the collective dynamics of quasi-one-dimensional domain structures in lipid bilayers interacting with the environment. The objective is to study the mechanisms of the directed energy transport in liquid crystalline lipid membranes.Methods. In this paper, the percolation domain structures formed as a result of phase separation in multicomponent lipid membranes are considered to be quasi-one-dimensional domain structures. The model distinguishes two subsystems interacting with each other and differing in their structural and dynamic properties, i.e., the membrane surface formed by polar groups of lipid molecules and the internal hydrophilic region of the membrane formed by acyl chains of lipids. The acyl chain subsystem is simulated using the Ginzburg-Landau Hamiltonian which considers the dependence of its dynamics on temperature close to the lipid melting phase transition temperature Tc.Results. Analysis of dynamic states has shown that elastic excitations moving at constant rate in the form of solitons may exist near temperatures Tc in the considered quasi-one-dimensional domain structures. In addition, motion of the elastic excitation region (kink) along domain structures in the acyl chain region causes the formation of acoustic soliton, i.e., the compression region in the polar group subsystem moving in concert with the kink displacement. The soliton localization region covers about 10 molecules and depends significantly on the interaction parameter of the polar group and acyl chain subsystems. Soliton moves at a subsonic speed determined, in particular, by the magnitude of an external force.Conclusions. The model developed in this paper shows that liquid crystalline domain structures in lipid membranes exhibit properties of active media, wherein the formation and displacement of localized elastic excitations on macroscopic spatial and temporal scales may occur. The proposed molecular mechanism of the soliton transport along quasi-one-dimensional domain structures may be used for describing the directed energy transfer along lateral domain channels in biomembranes and the cooperative functioning of the membrane bioenergetic and receptor complexes.